The Mediating Role Of Operational Efficiency And Transparency In The Relationship Between Digitalization Adoption And Job Satisfaction In The Purchasing Department In Bali - Vardhana, Gede; Nurmalasari, Made Ratih (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of digitalization adoption on job satisfaction in the purchasing department within Bali’s hospitality sector, with operational efficiency and transparency as mediating variables. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 136 procurement professionals. The findings indicate that digitalization adoption has a positive and significant effect on operational efficiency and transparency, which in turn significantly influence job satisfaction. Operational efficiency improves employees’ ability to complete tasks faster and reduces administrative burdens, thereby minimizing burnout and enhancing work-life balance. Meanwhile, transparency and traceability play a more dominant role by providing clear audit trails and role clarity, reducing uncertainty and preventing a culture of blame among employees. Furthermore, digitalization adoption also directly affects job satisfaction, although the indirect effects through mediating variables are stronger. The mediation analysis confirms that both operational efficiency and transparency significantly mediate the relationship between digitalization adoption and job satisfaction, with transparency emerging as the most influential factor. These findings support the Resource-Based View (RBV), emphasizing that technological resources must be transformed into organizational capabilities to enhance human resource outcomes. Overall, this study highlights that digital transformation in procurement is not merely a technological upgrade but a strategic approach to improving employee well-being and retention in the hospitality industry